BIOLOGICAL THERAPY IN CHRONIC RHINOSINUSITIS WITH NASAL POLYPS: A LITERATURE REVIEW OF TREATMENT METHODS INCLUDING DUPILUMAB AND MEPOLIZUMAB - Malwina Wojtas; Bartłomiej Czerwiec; Adam Borsuk; Julia Skowrońska-Borsuk; Martyna Narożniak; Adrianna Ewa Pękacka; Joanna Pergoł; Julia Borkowska; Zuzanna Krupa; Julia Sposób (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and purpose: Nasal polyps occur in chronic mucosal inflammation of the nasal cavity. Overgrown mucosa forms pale colored, smooth, lobular, poorly vascularized structures which expand into nasal cavity causing obstruction, nasal congestion and hyposmia. Corticosteroids used topically or systemically significantly improve patients’ quality of life by reducing the size of the polyps, however long-term steroid use is associated with systemic side effects. Sinus surgeries alleviate breathing problems, however sinonasal symptoms can reoccur even 3 years after the surgery. Recently introduced biological treatment such as mepolizumab or dupilumab, showed itself effective and safe. Studies show that patients treated with dupilumab or mepolizumab have lower risk of sinonasal symptoms reoccurrence.The aim of this review is to investigate the treatment methods in chronic rhinosinusitis with nasal polyps and the potential of the new biological therapy.Materials and methods: A literature review was conducted using databases including PubMed, Scopus and Google Scholar. Additionally, European position paper on rhinosinusitis and nasal polyps (2020) was used. Search terms included “chronic rhinosinusitis with nasal polyps”, “nasal polyposis”, “endoscopic sinus surgery”, “mepolizumab”, “dupilumab”.Summary and Conclusions: Steroid therapy and endoscopic sinus surgery as a well-known form of therapies alleviate symptoms of chronic rhinosinusitis with nasal polyps although often do not offer sustain outcomes. New studies concerning biological therapy including dupilumab and mepolizumab suggest a potential breakthrough for patients. Reoccurrence rate was significantly lower, and symptom control enhanced due to biological therapeutics. Dupilumab and mepolizumab should be considered in CRSwNP treatment.